Zur Einzelsprachenspezifik wissenschaftlichen Sprachausbaus im gnoseologischen Funktionsbereich von Sprache - Thielmann, Winfried (Linguistik Online, 2012)
This paper attempts to demonstrate that academic research depends, to a certain degree, on the language in which it is conducted. The reason for this is that European languages have, due to their typological differences, different histories of linguistic expansion (Sprachausbau). As can be shown for German and English, the purpose of naming the object of investigation in academic research is served by linguistic devices of very different nature. This may lead to different conceptions of the object of research and thus impact on the course of investigation.